Adoption and scaling out: strategies and experiences of the Forages for Smallholders Project - Roothaert, Robert; Kerridge, Peter C. (ITDG, 2004)
The Forages for Smallholders Project (FSP), convened by the International Centre for Tropical Agriculture (CIAT), started in 1995 to move research on tropical forages from the experiment stations to farmers’ fields, which created scope for evaluating the potential of improved forages in smallholder farming systems in Asia. The target farming systems were those in upland areas. The FSP now operates in six countries in Southeast Asia through national partners.